Induction of Rooting in Leafy Shoot Cuttings of Cinnamomum zeylanicum Breyn. by IBA - Thirunavoukkarasu, M. (Indian Forester, 1996)
Rooting trials were carried out using leafy shoot cuttings obtained from 3 month old coppices of Cinnamomum zeylanicum. Indole-3-butyric acid at concentrations of500, 1000 and 2000 ppm was used for induction of rooting. Successful rooting could be obtained to the extent of 80 percent with IBA 1000 ppm treatment. Untreated controls failed to root. The result shows that it can be multiplied by vegetative means with the aid of IRA for raising clonal plantations.